Ottawa Panel evidence-based clinical practice guidelines for therapeutic exercise in the management of hip osteoarthritis*. (October 2016) - Brosseau, Lucie; Wells, George A; Pugh, Arlanna G; Smith, Christine AM; Rahman, Prinon; Àlvarez Gallardo, Inmaculada C; Toupin-April, Karine; Loew, Laurianne; De Angelis, Gino; Cavallo, Sabrina; Taki, Jade; Marcotte, Rachel; et al.
Objectives: The primary objective is to identify effective land-based therapeutic exercise interventions and provide evidence-based recommendations for managing hip osteoarthritis. A secondary objective is to develop an Ottawa Panel evidence-based clinical practice guideline for hip osteoarthritis. Methods: The search strategy and modified selection criteria from a Cochrane review were used. Studies included hip osteoarthritis patients in comparative controlled trials with therapeutic exercise interventions. An Expert Panel arrived at a Delphi survey consensus to endorse the recommendations. The Ottawa Panel hierarchical alphabetical grading system (A, B, C+, C, D, D+, or D-) considered the study design (level I: randomized controlled trial and level II: controlled clinical trial), statistical significance ( p < 0.5), and clinical importance (⩾15% improvement). Results: Four high-quality studies were included, which demonstrated that variations of strength training, stretching, and flexibility exercises are generally effective for improving the management of hip osteoarthritis. Strength training exercises displayed the greatest improvements for pain (Grade A), disability (Grades A and C+), physical function (Grade A), stiffness (Grade A), and range of motion (Grade A) within a short time period (8–24 weeks). Stretching also greatly improved physical function (Grade A), and flexibility exercises improved pain (Grade A), range of motion (Grade A), physical function (Grade A), and stiffness (Grade C+). Conclusion: The Ottawa Panel recommends land-based therapeutic exercise, notably strength training, for management of hip osteoarthritis in reducing pain, stiffness and self-reported disability, and improving physical function and range of motion.